Properties of diamond films deposited by multi-cathode direct current plasma assisted CVD method - Lee, JK; Baik, YJ; Eui, KY; Park, JW (ELSEVIER SCIENCE SA, 2001)
Four diamond films were prepared by the multi-cathode direct current plasma-assisted chemical vapor deposition (DC-PACVD) method and optical and thermal properties were characterized. Optical transmission and thermal conductivity were strongly dependent on the power density and the methane concentration. Impurities such as, H, Na, Al, Si, K, Ca and Ta were detected by SIMS analysis. The Ta concentration in diamond films was found to be around 300 ppm by RES measurement and Ta inclusion originated from the Ta cathode kept above 2100 degreesC. Optical and thermal properties of the diamond film deposited with a growth rate of 4 mum/h at 0.37 kW/cm(2) (17 kW on phi 76 mm substrate) and 5% CH4 were similar to that of the type IIa natural diamond. (C) 2001 Elsevier Science B.V. All rights reserved.